Dressing control of three-mode entanglement in two cascaded four-wave mixing. (16th September 2016) - Zhang, Yufei; Zhang, Da; Zhang, Heyuan; Tang, Haijun; Cheng, Lin; Liu, Ruizhou; Zhang, Yanpeng
Abstract: We report the control of the dressed state in three-mode optical entanglement in an N-type four-level system using two cascaded parametric amplification four-wave mixing steps inside an atom-like optical cavity and injected by thermal optical fields: a coherent field and the Einstein–Podolsky–Rosen field. First, cavity dressing results in Aulter–Towns-like (AT-like peak) anti-squeezing. And the three-cavity dressing interaction induces multi-AT-like peaks. Meanwhile, the cavity enhanced nonlinear gain results in one squeezing dip polariton. In addition, the coupling of three enhanced nonlinear gains brings about multi-dip squeezing. Second, as two nonlinear coefficients change, the nonlinear phase makes the squeezing profile (in phase, amplification) turn into an anti-squeezing profile due to nonlinear loss (out of phase, de-amplification). Finally, the squeezing profile can also be modified by field dressing (AT splitting, enhancement and suppression), and the squeezing degree is affected by injection fields. Thus, by judging the squeezing of three nonseparability criteria, we get three-mode optical entanglement.